The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1177/00220345960750120901
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro Model of Human Dental Pulp Repair

Abstract: Abstract. Pulp tissue responds to dentin injury by laying down reactionary dentin secreted by existing odontoblasts or reparative dentin elaborated by odontoblast-like cells that differentiated from precursor cells in the absence of inner dental epithelium and basement membrane. Furthermore, growth factors or active dentin matrix components are fundamental signals involved in odontoblast differentiation. In vitro, dental pulp cells cultured under various conditions are able to express typical markers of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 51 publications
2
63
0
8
Order By: Relevance
“…This finding has relevant physiological consequences. Indeed in vivo, intracellular recordings have shown that odontoblasts have a resting membrane potential around Ϫ80 mV, values comparable with excitable cells (24). Previous electrophysiological studies have described the presence of ion channels in odontoblasts whose activity was modulated by mechanical stimuli (5).…”
Section: Sodium Channel Subunitsmentioning
confidence: 99%
“…This finding has relevant physiological consequences. Indeed in vivo, intracellular recordings have shown that odontoblasts have a resting membrane potential around Ϫ80 mV, values comparable with excitable cells (24). Previous electrophysiological studies have described the presence of ion channels in odontoblasts whose activity was modulated by mechanical stimuli (5).…”
Section: Sodium Channel Subunitsmentioning
confidence: 99%
“…16) Dentinal healing and repair are the result of successive and interrelated processes that include proliferation, chemotaxis, and differentiation of dental pulp cells into odontoblasts, leading to reparative dentin formation. 17) However, the underlying mechanism of TGF-b1 responsible for regulating hPDL cell migration has not been fully elucidated. Because hPDL cells are responsible for tissue regeneration and mineralized tissue matrix formation, and cell migration are critical processes in tissue regeneration, it is valuable to clarify the precise mechanism of the cell migration of hPDL cells.…”
mentioning
confidence: 99%
“…A espessura das fatias dentárias humanas constituiu-se, também, uma das preocupações, não pelo fato de se conseguir padronizar a espessura recomendada de 1,5 a 2mm 76,87,88,125 , mas em obter uma espessura adequada que proporcionasse, após os procedimentos de fixação e desmineralização, condições favoráveis para o corte histológico. Esse foi o nosso maior problema, pois inúmeras fatias dentárias foram perdidas durante esse procedimento.…”
Section: Vasosunclassified
“…Esse foi o nosso maior problema, pois inúmeras fatias dentárias foram perdidas durante esse procedimento. Os procedimentos de fixação (24h) e desmineralização (48h-72h) foram seguidos conforme dita o protocolo do Dr. Antony Smith e outros trabalhos referentes `a cultura de fatias dentárias 76,81,88,125 . Segundo informação do técnico Chris Strayhorn (Universidade de Odontologia de Michigan), o qual realizou os procedimentos histotécnicos referentes ao corte das amostras em parafina e coloração com HE, o problema das perdas das amostras poderia estar relacionado com a espessura da fatia dentária o qual, no primeiro experimento, foi de 2mm.…”
Section: Vasosunclassified
See 1 more Smart Citation